(untitled) (Medico Legal Update, 2019)
One of the common regional injuries an individual can sustain in Road Traffic Accidents is head injury. Head and face is the region which is more susceptible and requires an immediate care and treatment. The fatality rate is high even with intense treatment. Law making agencies has been continuously trying to enforce the rules of wearing helmets both in riders and pillion in two wheelers. Considering the same, this study was done in eastern part of Bangalore, an IT hub and a rapidly developing area with increase in vehicular movements. The study concluded that incidence was common among age group of 21-30 years with male predominance and among two wheel riders. Laceration is most common external injury followed by abrasion. Fissure fractures are most common type of Fracture, and sub dural haemorrhage is seen in majority of cases.